1998
DOI: 10.1093/emboj/17.12.3233
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of polyomavirus internal protein VP2 with the major capsid protein VP1 and implications for participation of VP2 in viral entry

Abstract: A complex of the polyomavirus internal protein VP2/ VP3 with the pentameric major capsid protein VP1 has been prepared by co-expression in Escherichia coli. A C-terminal segment of VP2/VP3 is required for tight association, and a crystal structure of this segment, complexed with a VP1 pentamer, has been determined at 2.2 Å resolution. The structure shows specific contacts between a single copy of the internal protein and a pentamer of VP1. These interactions were not detected in the previously described struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
184
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(192 citation statements)
references
References 32 publications
8
184
0
Order By: Relevance
“…It was previously reported that the N terminus of polyomavirus VP2 protein was found to be modified by myristylation (Streuli & Griffin, 1987) and studies of VP2 myristylation-defective mutants of polyomavirus demonstrated that VP2 plays a role in the early events of virus entry (Krauzewicz et al, 1990 ;Sahli et al, 1993). In addition, a recent study, utilizing a prokaryotic-expressed truncated VP2 protein interaction with VP1 protein, has revealed that the N terminus of VP2 is flexible and possibly exposed at the virion surface, and may be involved in virus entry (Chen et al, 1998). Whether the VP2 protein has the ability to cause a conformational change in the VP1 protein structure, exposing the proper VP1 epitope for cell attachment, or whether the exposed N terminus of VP2 protein is directly involved in virus entry is still to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that the N terminus of polyomavirus VP2 protein was found to be modified by myristylation (Streuli & Griffin, 1987) and studies of VP2 myristylation-defective mutants of polyomavirus demonstrated that VP2 plays a role in the early events of virus entry (Krauzewicz et al, 1990 ;Sahli et al, 1993). In addition, a recent study, utilizing a prokaryotic-expressed truncated VP2 protein interaction with VP1 protein, has revealed that the N terminus of VP2 is flexible and possibly exposed at the virion surface, and may be involved in virus entry (Chen et al, 1998). Whether the VP2 protein has the ability to cause a conformational change in the VP1 protein structure, exposing the proper VP1 epitope for cell attachment, or whether the exposed N terminus of VP2 protein is directly involved in virus entry is still to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…This single protein, arranged as 72 pentamers, forms the shell surrounding the viral genome (Liddington et al 1991;Stehle et al 1994). Each VP1 pentamer engages the internal protein VP2 or VP3 via hydrophobic interactions (Chen et al 1998). Additionally, VP1 binds directly to its DNA genome harbored within the viral particle (Carbone et al 2004).…”
Section: Polyomavirus Co-opts the Er During Entrymentioning
confidence: 99%
“…One VP2 (and VP3) protein binds to the hydrophobic inner cavity of one VP1-capsomere via a conserved hydrophobic region close to the C-terminal of VP2, forming a VP1:VP2 capsomere complex (Barouch and Harrison 1994;Chen et al 1998) (Figure 2.3). While the hydrophobic binding Encapsidation has been achieved by either co-expression of VP1 and foreign protein fused VP2/VP2C within insect cells (Boura et al 2005;Inoue et al 2008), or by separate expression in E.coli and separate chromatographic purification before co-assembly in vitro (Abbing et al 2004).…”
Section: Protein Encapsidation By Mpyvmentioning
confidence: 99%
“…shown that a segment of the C-terminus of VP2 protein can bind to at least three VP1 subunits inside a capsomere (VP1 pentamer) cavity via a hydrophobic binding site (Figure 4.1) (Barouch and Harrison 1994;Chen et al 1998). Fusion of GFP protein at the N-terminus of VP2 was attempted to encapsidate GFP inside the MPyV VLP.…”
Section: Encapsidation Is Achievable By Utilising a Segment Of The C-mentioning
confidence: 99%
See 1 more Smart Citation